PENGARUH MODIFIKASI PERMAINAN SEPAKBOLA TERHADAP KERJASAMA SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN (STUDI PADA SISWA KELAS XI SMAN 1 KESAMBEN JOMBANG) - HARDIYANTO, TRI (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract In Physical education learning teaching material delivered very influential on student learning outcomes in terms of both physical and character education. Teaching materials should bein accordance with the conditions of the facilities and infrastructure available in schools and ease students receive materials need to be considered. One way to make the material more easily accepted students is to implement modifications of football game in learning physical education. Modifications of football game are expected to apply in Physical education are able to maximize learning physical education special cooperation of students. This study aimed to determine the effect of modification of the game of football again ststudent collaboration in learning physical education, sport and health. This research is experiment to with descriptive quantitative approach. The population in this study were students of SMAN 1 Kesamben Jombang and the samples totaling 67 students, which consisted of 33 students of class XII PS 2 in to the experimental group and 34 students of class XII PS 1 a control group using a random cluster sampling technique. This study instrument using a questionnaire cooperation and data analysis using t test. From the results of statistical calculations it can be concluded that there is a significant effect modification football game against the cooperation of students in learning physical education, sport and heal this evident from the value of t count 2,179 > t table1,990 with a significance level of 0.05. While the effect of 7.01%. Keywords: Modification, football game, Student Cooperation, Physical education.